Efektifitas Prenatal Gentle Yoga Dalam Mengurangi Keluhan Nyeri Punggung Bawah Pada Ibu Hamil - Ayu Rosita Dewi; Dika Yanuar Frafitasari; Dwi Margareta Andini (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
During pregnancy, a woman must be able to adapt to various physical changes that often occur and can cause uncomfortable conditions, such as back pain which begins to be felt in the second and third trimesters. If this condition is not treated immediately, it can cause anxiety and disruption to the pregnant woman's activities. As a way to reduce complaints of back pain, pregnant women can do prenatal gentle yoga exercises. This study aimed to assess the effectiveness of prenatal yoga in reducing pain in the lower back of pregnant women at the Ngletih Community Health Center, Kediri City. This study aims to assess the effectiveness of prenatal yoga in reducing pain in the lower back of pregnant women at the Ngletih Community Health Center, Kediri City. Research method: This research adopted a quantitative design with a Pre-Experimental design, using the One Group Pretest-Posttest method. The sample of pregnant women in the second and third trimesters was 31 respondents. The sampling method involved Total Sampling and the use of a pain level measuring tool with the Numeric Rating Scale (NRS), while data analysis used the Wilcoxon Test. Research Results: Before carrying out prenatal yoga exercises, the majority of pregnant women felt lower back pain on a mild scale, the number of respondents was 17 (54.8%). After doing prenatal yoga exercises twice in 2 weeks, the majority of pregnant women no longer felt back pain, the number of respondents was 18 pregnant women (58%). The p-value of the analysis using the Wilcoxon test is 0.000.